Prevalence of dental caries in the primary, mixed and permanent dentitions in Nigeria: A systematic review and meta-analysis - Folahanmi Tomiwa Akinsolu; Olunike Rebecca Abodunrin; Abel Chukwuemeka; Mobolaji Timothy Olagunju; Ifeoluwa Eunice Adewole; Abideen Olurotimi Salako; George Uchenna Eleje; Adebola Oluyemisi Ehizele; Joanne Lusher; Foluso Owotade; Oliver Chukwujekwu Ezechi; Moréniké Oluwátóyìn Foláyan (PLoS ONE, 2026)
Background The national prevalence of dental caries in Nigeria is currently unknown. The objective of this systematic review and meta-analysis was to determine the prevalence of dental caries in the primary, mixed and permanent dentition among residents in urban, rural and semi-urban Nigeria. Methods A systematic search was conducted in PubMed, Web of Science, Scopus, CINAHL and Embase databases and Google Scholar for studies published between January 2001 and December 2023 reporting the prevalence of dental caries in Nigeria. The review was registered with PROSPERO (CRD42022362019) and conducted in accordance with the PRISMA guidelines. Data extracted included study design, sample size, age of participants, and study location. Study quality and risk of bias were assessed. A random-effects meta-analysis was performed to estimate pooled prevalence. Results A total of 1,010 records were identified, of which 52 studies were included in the systematic review and 35 were eligible for meta-analysis. Most studies were conducted in Southwestern Nigeria. The overall pooled prevalence of dental caries in Nigeria was 17% (95% CI: 14%–21%; I² = 97%). The pooled prevalence was 16% (95% CI: 10%–24%; I² = 98%) in primary dentition, 16% (95% CI: 11%–23%; I² = 97%) in mixed dentition, and 20% (95% CI: 16%–26%; I² = 96%) in permanent dentition. By setting, the pooled prevalence was 22% (95% CI: 7%–52%; I² = 98%) in rural areas, 17% (95% CI: 14%–22%; I² = 97%) in semi-urban areas, and 14% (95% CI: 6%–29%; I² = 98%) in urban areas. Substantial heterogeneity was observed across studies. Conclusion Dental caries remains a significant public health concern in Nigeria, affecting approximately one in five individuals. Although variations were observed across dentition types and geographic settings, substantial heterogeneity indicates diverse epidemiological contexts across the country. Strengthened preventive strategies and improved access to oral healthcare services are needed to address the burden of dental caries nationwide.